Pengaruh Kualitas Audit, Prior Opinion, dan Pertumbuhan Perusahaan Terhadap Opini Going Concern - Primoso Pebrianto; Ayatulloh Michael Musyaffi; Tri Hesti Utaminingtyas (LPPM Universitas Negeri Jakarta, 2025)
This study aims to explore the relationship between going concern audit opinion and audit quality, past opinion, and firm growth. Samples of 24 businesses and 72 sets of data were obtained from mining companies that were listed on the Indonesia Stock Exchange in 2020–2022 over the course of the three-year study period. For data analysis, logistic regression was used with SPSS version 29. The findings demonstrated that going concern opinion is not impacted by audit quality or business progress, but rather is impacted by prior opinion.